Aplikasi Website Peminjaman Perpustakaan Menggunakan Bootstrap (Studi Kasus pada SMK Pasundan Rancaekek) - Siti Fitriyani; Harry Pribadi Fitrian (Institut Shanti Bhuana, 2024)
School libraries often face problems such as difficulties in recording book borrowing and returns, as well as challenges in finding information about book availability. To address this issue, a web-based solution is proposed. A web-based library loan application using Bootstrap is designed to simplify the process of borrowing and returning books, providing convenience for administrators in managing the library. This research includes several methodological stages: literature study, needs analysis, system design, development and testing. The results show that the use of Bootstrap successfully created a responsive and user-friendly application interface, the application features function according to requirements, and the intuitive interface makes it easier for users and administrators to manage the library. In conclusion, this application can improve efficiency in the book borrowing and returning process, and provide convenience for administrators in managing the library.